Manejo de residuos domiciliarios, condiciones de vivienda y salud en la comunidad Huitoto Murui Muiname. Loreto, 2024 - Flores Cardenas, Josias (2025)
It is a quantitative, descriptive and correlational study, with the purpose of evaluating household waste management practices and their impact on housing and health conditions in the Negro Urco community of the Huitoto Murui Muiname ethnic group. The study population is all families/homes with an approximate population of 700 inhabitants, the study unit is the number of homes/homes, made up of 104 family homes, the sampling was census type. Data collection was carried out through surveys with a reliability level of Cronbach's alpha coefficient, 0.783. The normality of the data was determined with the Kolmogorov-Smirnov test, which reports that none of the dimensions evaluated has a normal distribution, so the Spearman correlation had to be used for the statistical analysis, which allowed us to conclude: That the current waste management practices in the Negro Urco community are insufficient, especially with regard to the separation, treatment and final disposal of waste; It prevails from incineration and the use of uncontrolled landfills that generate negative impacts on public health and the environment. Health conditions in homes are perceived to be in good hygiene conditions, but the lack of adequate treatment of household waste and low participation in waste separation negatively affect the quality of air, water and the general environment. Regarding air and water quality, it reflects concern about the environmental effects of poor waste management. Community participation in waste management is limited, despite recognizing the importance of these practices. There is acceptance of the importance of promoting healthy homes as an integral part of waste management, considering that this approach is essential to promote public health in rural communities.